Calculation of Gamma-ray Attenuation Parameters for Locally Developed Ilmenite-magnetite (I-M) Concrete (Journal of Bangladesh Academy of Sciences, 2016)
The mass attenuation coefficients (?/?) of locally developed ilmenite-magnetite (I-M) concrete over a wide range of photon energy were calculated analytically using Matlab and compared with the values obtained from widely used XCom computer program. A good agreement between the calculated and XCom generated value was found. The linear attenuation coefficients and relaxation lengths were calculated for the same energy range. The transmission curves were drawn for some common gamma-ray energies and half value layer and tenth value layer were calculated. The results of this study will provide some useful information about the shielding material data base for practical shielding calculation. The results will also illustrate the effectiveness of I-M concrete so far as its shielding properties are concerned.Journal of Bangladesh Academy of Sciences, Vol. 40, No. 1, 11-21, 2016